دور إدارة التخزين في تحسين إنتاجية المؤسسة الصناعيةالجزائرية دراسة حالة مؤسسة "الرياض سطيف"، فرع: "مطاحن الحضنة" Groupe Eriad Setif, Filiale Les Moulins Du Hodna, M'sila خلال الفترة الممتدة (2010-2014) - عزوز, منير; برحومة, عبد الحميد (جامعة الوادي - University of Eloued, 2018)
تعتبر إنتاجية المؤسسة أحد أهم الموضوعات والمسائل التي تسعى المؤسسات الصناعية إلى دراستها من خلال البحث في سبل تحسين أدائها بإشراك مختلف الإدارات والأقسام التي يتشكل منها هذا الكيان، كون أن مرحلة الإنتاج والتحويل تمثل محور نشاط المؤسسات الصناعية والعنصر الرئيسي المستخدم في توليد المداخيل والوصول إلى الأهداف في ظل تحقيق استمرارية في النشاط، والفكرة الأساسية لهذه الدراسة هو تبيان أهمية ودور إدارة التخزين في تحقيق هذا المسعى من خلال عرض وتوضيح مساهمتها –إدارة التخزين- في تطوير وتحسين كفاءة المؤسسة والرفع من إنتاجيتها مع ضمان الالتزام بانجاز البرامج المخططة دون تسجيل انحرافات، حيث أوضحت الدراسة أن إدارة المخزون وبحكم تدخلها في مختلف المراحل الإنتاجية عبر استخدام مختلف أساليب وطرق التسيير والسيطرة على المخزونات لها علاقة ارتباط مباشرة بإدارة الإنتاج، وعليه يجب تحليل هذه العلاقة وتوجيهها بما يخدم أهداف المؤسسة من جهة ويحسن من أدائها الإنتاجي من جهة أخرى. Enterprise productivity is one of the most important topics and issues that industrial enterprises endeavor to study, through the search of ways to improve their performance by involving various departments and divisions that form the mentioned entity, to the fact that the production and conversion stage represents the axis of activity of the industrial enterprises and the main element used in the income generation, therefore achievement of objectives in light of the continuity in activity. The basic idea of this study is to demonstrate the importance and the role of stock management in this endeavor by presenting and clarifying its contribution to the development and improvement of the efficiency of organization therefore, the increase in productivity while ensuring adherence with the completion of the planned programs without deviations; hence, this study has shown that the stock management and by virtue of its involvement in various production stages through the use of multiple management techniques and methods, and the control of stocks have a direct relation to the production management; thereupon this relationship must be analyzed and directed in a way to serve the goals of the organization and therefore, improves the performance of the production.
The Role of Stock Management in Improving the Productivity of the Algerian Industrial Enterprise- A Case of: Riyadh Setif, Branch: Al Hodhna Mills during the (2010-2014)
مقال
Keywords: إدارة التخزين؛ الإنتاجية؛ المؤسسة الصناعيةالجزائرية